2021
DOI: 10.3389/fpsyg.2021.623646
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Early Maladaptive Schemas as Predictors of Cyber Dating Abuse: An Actor-Partner Interdependence Mediation Model Approach

Abstract: The increasing role that new technologies play in intimate relationships has led to the emergence of a new form of couple violence, cyber dating abuse, especially among adolescents and young adults. Although this phenomenon has received increased attention, no research has investigated predictors of cyber dating abuse taking into account the interdependence of the two partners. The study examines adverse childhood experiences (abuse, neglect, and witnessed intimate partner violence) and early maladaptive schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 72 publications
1
12
1
Order By: Relevance
“…Perpetration of EDV may be best attributed to reactive emotional aggression compared to proactive instrumental aggression ( Branson and March, 2021 ). Additionally, our results were inconsistent with the outcomes of Celsi et al (2021) , which indicated that abandonment was not considered a possible predictor of young adults’ perpetration of EDV. Instead, emotional deprivation and childhood experiences (i.e., abuse, neglect, and witnessing IPV) are possible predictors of perpetrated and suffered EDV, whereby more frequent experiences of emotional abuse and physical neglect during childhood were indirectly related to an increased likelihood of perpetrating EDV among both sexes.…”
Section: Discussioncontrasting
confidence: 97%
“…Perpetration of EDV may be best attributed to reactive emotional aggression compared to proactive instrumental aggression ( Branson and March, 2021 ). Additionally, our results were inconsistent with the outcomes of Celsi et al (2021) , which indicated that abandonment was not considered a possible predictor of young adults’ perpetration of EDV. Instead, emotional deprivation and childhood experiences (i.e., abuse, neglect, and witnessing IPV) are possible predictors of perpetrated and suffered EDV, whereby more frequent experiences of emotional abuse and physical neglect during childhood were indirectly related to an increased likelihood of perpetrating EDV among both sexes.…”
Section: Discussioncontrasting
confidence: 97%
“…Only one of the reviewed studies examined the relationship between childhood physical abuse and cyber dating abuse (3.1%), finding neither a direct nor an indirect relationship, through the mediation of early maladaptive schemas, between childhood physical abuse and cyber dating abuse [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Perpetrated and suffered CDA within the current romantic relationship was measured through a scale previously validated in Italy by Celsi et al (2021) . The scale consists of 40 items (20 for perpetration and 20 for victimization) assessing two dimensions of CDA: monitoring and control (11 items, e.g., “I/my partner checked my/my partner’s location and online activities”; α = 0.86 and 0.89 for perpetration and victimization, respectively) and psychological or sexual pressure and aggression (9 items, e.g., “I/my partner sent a threatening message to my partner/me”; α = 0.84 and 0.78 for perpetration and victimization, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Physical and psychological IPV perpetrated by parents and witnessed by respondents during their childhood was assessed through a 6-item measure by Celsi et al (2021) . Three items measured violence perpetrated by the mother against the father and three items assessed violence perpetrated by the father against the mother (e.g., “I saw/heard my mother/father being insulted, denigrated, humiliated, or verbally assaulted by my father/mother”; α = 0.71 and 0.84 for violence perpetrated by mothers and fathers, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation